Culture of domestic cat ovarian tissue in vitro and in the chick embryo chorioallantoic membrane - Vilela, J. M.V.; Leonel, E. C.R. [UNESP]; D'Oliveira, L.; Paiva, R. E.G.; Miranda-Vilela, A. L.; Amorim, C. A.; Pic-Taylor, A.; Lucci, C. M. (Elsevier, 2016)
In vitro culture and transplantation procedures are essential protocols employed in the evaluation of ovarian follicle survival and development. Culture in the chorioallantoic membrane (CAM) of chick embryos is an intermediate method that provides important follicle development information and has not been tested for cat ovaries to date. The aim of this study was to investigate if in vitro and CAM culture could be used as short-term systems to study cat ovarian tissue development. The ovaries of eight cats were dissected into 3-mm3 cubes, cultured in vitro and in CAM for up to 5 days, and stained with hematoxylin-eosin and Gomori trichrome. Cell proliferation was analyzed using anti-Ki67. Possible differences among groups were investigated by analysis of variance or the Kruskal–Wallis test followed by Bonferroni correction. The T-test or Wilcoxon test was used to verify differences between the CAM and IVC. Results revealed that 87.5% of all follicles were primordial during culture. The percentage of primordial follicles in the morphologically normal follicles (MNF) pool was always higher than 80%, with the exception of Day 3 of CAM culture, but the number of MNF reduced significantly from Day 0 (600 out of 777 follicles) to Day 5 in the CAM (91 out of 171) and IVC (296 out of 686). The number of primordial follicles in 1 mm3 in Days 2, 3, and 5 in the CAM was significantly lower than that in the control (Day 0). No cellular proliferation was observed in culture. Vascularization occurred in the CAM culture, but with no association to follicular viability. In addition, both methods showed an increase in connective tissue during culture. Although no significant differences were observed in the percentage of MNF, there was a reduction in the total number of follicles, both for IVC and CAM-cultured ovarian tissue. Furthermore, anti-Ki67 did not stain any follicle after Day 0 in IVC or in CAM culture. Neither system was capable of promoting follicle growth and/or development. The results show that the CAM is not a suitable system for feline ovarian tissue and highlight the necessity to improve IVC systems in cats.
Keywords: Cell proliferation; Culture in ovo; Development; Feline; Preantral follicle; Viability